The Effectiveness of Reciprocal Peer Tutoring In Supporting Blended Learning in Both Online and Offline Modes - Mohamad Hanefar, Shamsiah Banu; Wong, Ling Shing; Chan, Chang Tik (INTI International University, 2011)
Millennium age education is moving out from traditional education (teacher-Centered Learning) to contemporary education which is moving towards Students-Centered Learning (SCL). One of the widely being discussed and practiced SCI by educators and students is Blended Learning (BI). This paper will look into the effectiveness of one of the BL approach which Is Reciprocal Peer Tutoring (RPT). The study was done to measure the effectiveness of reciprocal peer tutoring in supporting blended Learning In both online and offline modes and as well as to get the students’ feedback on the usage of blended learning. The research was conducted in varies faculties In INTl International University, Nilai Campus for the period of one semester. The students were divided into two major group; IT group arid non-IT group. The study revealed that the majority of the students had a positive view in the usage of RPT in offline mode and in online mode even though the result showed that group without RPT scored slightly higher than with RPT group. The researchers believed that RPT could be a good toot to a better Leaching and learning environment especially in today’s Malaysian higher educational institution.